Exxonmobil's social responsibility messaging – 2002–2013 CEO letters. Issue 3 (3rd July 2018) - Grantham, Susan; Vieira, Edward T.
ABSTRACT: The purpose of this study was to evaluate ExxonMobil's social responsibility/social responsiveness (SR) communication to determine the company's social responsibility messaging in terms of the Social Responsibility themes of the Triple bottom Line Model (profit, people, planet) and to evaluate if the messaging changed in response to external events such as the 2007 financial crisis and 2010 BP oil spill. ExxonMobil's CEO letters included varying levels of emphasis on SR content related to profit and planet. The analysis showed a reduced focus on profit following the 2007 financial crisis and an increased focus on the planet following the 2010 BP oil spill.